SOME ASPECTS OF EPIDEMIOLOGY, PATHOGENESIS, DIAGNOSIS AND TREATMENT OF MULTIPLE MYELOMA - S.N. ABDULLAEVA (Avicenna Tajik State Medical University, 2021)
A literature review article provides a comprehensive overview of literature related to epidemiology, pathogenesis, diagnosis and treatment of multiple myeloma (MM). Literature data show that MM has unclear patterns of the disease distribution, and there are trends in rising incidence. Although the aetiology of MM is not fully understood, according to most researchers, risk factors (RFs) leading to a progressively high incidence of MM include advanced age, male gender, exposure to harmful environmental factors (ionising radiation, chemical agents), family predisposition, an increased prevalence of autoimmune diseases and obesity. MM is characterised by the absence of specific clinical manifestations and similarity with other conditions, which is one of the factors associated with delay in diagnosis of MM. Damage to internal organs, particularly the heart and kidneys, a frequent complication of MM, leads to mutual burdening and is also one of the factors of adverse outcomes early during the disease. The International Myeloma Working Group (IMWG) diagnostic criteria and additional investigation techniques allow high accuracy to diagnose MM and its complications. Despite the development and introduction of new drugs and treatments, the long-term survival rates in MM patient remains low. Therefore there is a need for further research in this direction.